Analysis Of Work Motivation, Work Discipline And Organizational Culture On Employee Perfomance Of Satuan Polisi Pamong Praja Kabupaten Karo - Aditya Secchal Suranta Tarigan; Abdi Setiawan; Saimara AM Sebayang (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the extent to which work motivation, work discipline and organizational culture impact the perfomance of employees of Satuan Polisi Pamong Praja Kabupaten Karo. The population in this study all 219 employees of Satuan Polisi Pamong Praja Kabupaten Karo with the Slovin formula used to determine the sample size, which was 69 respondents. This study was conducted 2025 with a quantitative-based primary data approach through the distribution of questionnaries. The data obtained were the analyzed using SPSS 25 with a multiper linier regression method. Based on the result of the study, work motivation, work discipline and organizational culture have a positive and significant effect employee perfomance, both partially and simultaneously. Of the three variabels, in the multiple linier regression test, work motivation has the most dominant impact with the highest Standadized Coeffucients Beta value of 0,336. The four pruposed hypotheses (H1, H2, H3, H4) were successfully proven true and accepted because the results  of the study support the initial assumptions. The Adjusted R Square figure for employee perfomance is 64,5%, of which can be explained by  work motivation, work discipline and organizational culture, while the reamining 35,5% is explained by other factors or variables outside the model. The relationship between employee perfomance and work motivation, work discipline and organizational culture shows a very strong and significant correlation.